Retrospective survey for clinical course and aggravating factors of adolescent atopic dermatitis in two years' cohort study on first‐year university students - Mayuko Nakano‐Tahara; Mai Matsumoto; Keiko Yamauchi‐Takihara; Hiroyasu Iso; Ichiro Katayama; Hiroyuki Murota (Journal of Cutaneous Immunology and Allergy, 2022)
Abstract Background Recent epidemiological studies have revealed increased numbers of adolescent subjects with atopic dermatitis, most of who experienced chronic symptoms since childhood. However, the complete clinical nature of atopic dermatitis in Japanese adolescents is poorly understood. We conducted this study to accumulate knowledge of factors contributing to protracted atopic dermatitis symptoms in adolescent subjects to avoid an unfavorable clinical outcome in these patients. Methods On 2013 and 2014, first‐year students at our university answered a retrospective self‐questionnaire about their demographic characteristics and past history of allergies. Answers from 6105 respondents were analyzed. Subjects with atopic dermatitis were divided into four groups according to their clinical courses, and factors potentially influencing their clinical courses were identified. Results Nearly 16% of the students had a history of diagnosed atopic dermatitis, many of who had experienced symptoms since childhood (protracted course). Other respondents had experienced remission (32%), adolescent onset (14%), or recurrence (6%). Logistic regression analysis found that psychological stress and air dryness were apparent exacerbating factors that increased the risk of the protracted, recurrent, and adolescence courses. Furthermore, sleep loss, house dust, pollen, high temperature, and sweat were the aggravating factors associated with the protracted course alone. Conclusions We found that a high proportion of Japanese adolescent subjects with atopic dermatitis had experienced protracted symptoms and further identified factors that may have led to this unfavorable course. We expect that limiting these factors in this population might alleviate the subjects' chronic symptoms.